Late prehistoric copper smelting in the Lao PDR: Experimental reconstruction based on the Vilabouly Complex evidence. (June 2021) - Cadet, Mélissa; Tereygeol, Florian; Sayavongkhamdy, Thongsa; Souksavatdy, Viengkeo; Luangkhoth, Thonglith; Chang, Nigel; Dillmann, Philippe; Pryce, T.O
Highlights: Macro, micro and compositional archaeological results suggest co-melting at the Vilabouly Complex. Experimental field reconstruction of co-smelting in open-internally heated crucibles. Co-smelting of malachite and chalcocite gave successful smelts comparable to Vilabouly Complex evidences. Abstract: Field experiments in copper smelting were carried out in order to test assumptions about the copper production processes employed at the Vilabouly Complex (VC), an Iron Age extraction and production site in central Laos. VC is one of only three primary production sites known in Southeast Asia and appears to be a major copper production and mining locale. Analytical results on the VC assemblage (ores, crucibles, slag fragments and copper alloy objects), along with the geological information, allowed us to generate hypotheses on the smelting process. The identification of macroscopic layers of matte associated with copper suggests the introduction of sulfidic ores during the process. Co-smelting with carbonate ores (likely malachite) and a secondary copper sulfide, chalcocite (Cu2 S), seemed to be most likely. Therefore, experimental reconstructions were performed to test this co-smelting of malachite with chalcocite in a one step-process using crucibles based on the archaeological examples as reaction vessels. The experiments produced matte, of different compositions according to the charge used, along with metallic copper and slag. The ratio (1:1) of malachite/chalcocite resulted in products comparable to the Vilabouly Complex evidence and thus strengthens the hypothesis.